Oral history interview with Louis Schmier, March 4, 2004 - Schmier, Louis (Valdosta State University Archives and Special Collections, 2004)
Oral history interview with Louis Schmier, March 4, 2004. Valdosta (Ga.). Fieldworker: Jenna Switzer. Audio file digitized from 2 cassette tapes. Part of the South Georgia Folklife Project at Valdosta State University Archives and Special Collections. Discussion about Dr. Schmier's life and his religious, ethnic, and cultural practices. Semester project for HON 3990B, Folklore and Fieldwork, spring 2004, Laurie Sommers. Schmier is also included in PRJ 1010 as part of Sounds of South Georgia Series.
1 electronic record(s) and derivatives. 2 audio file (wav, mp3), combined. 449,177,688 bytes. 00:42:11. 3 PDF documents (15 scans, jp2). 645 MB (677,279,133 bytes).
Keywords: Oral histories; Sound recordings; Valdosta (Ga.); Lowndes County (Ga.); Jews; Judaism--Customs and practices; Seder; College teachers; Ethnic food